2006
DOI: 10.1136/gut.2005.086900
|View full text |Cite
|
Sign up to set email alerts
|

Pit patterns in rectal mucosa assessed by magnifying colonoscope are predictive of relapse in patients with quiescent ulcerative colitis

Abstract: Background: Relapse of ulcerative colitis is difficult to predict by routine colonoscopy. A high-resolution video-magnifying colonoscope with chromoscopy enables the observation of colorectal mucosal pit patterns. Aims: To investigate the association of pit patterns as assessed by magnifying colonoscopy (MCS) with histological inflammation and mucosal chemokine activity in patients with quiescent ulcerative colitis, and to prospectively analyse the prognostic factors that may predict exacerbations. Methods: MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…[4][5][6] Other studies have reported the features of magnifying colonoscopy to be associated with the histological activity of UC and the prediction of disease relapse. 7,8 In the present study we investigated whether relapse of disease within 12 months could be predicted by precise observation of the surface colonic mucosa, especially by the findings of small defects, fine network, and crypt opening pattern on the surface epithelial mucosa by magnifying colonoscopy in patients with quiescent UC. Moreover, we compared the relationship between magnifying colonoscopic and histological findings.…”
mentioning
confidence: 99%
“…[4][5][6] Other studies have reported the features of magnifying colonoscopy to be associated with the histological activity of UC and the prediction of disease relapse. 7,8 In the present study we investigated whether relapse of disease within 12 months could be predicted by precise observation of the surface colonic mucosa, especially by the findings of small defects, fine network, and crypt opening pattern on the surface epithelial mucosa by magnifying colonoscopy in patients with quiescent UC. Moreover, we compared the relationship between magnifying colonoscopic and histological findings.…”
mentioning
confidence: 99%
“…38 Moreover, Nishio et al investigated the association of pit patterns as assessed by magnifying endoscopy with histological inflammation and mucosal chemokine activity in patients with quiescent UC. 39 In that study, magnifying endoscopic grading was associated the degree of histological inflammation and mucosal interleukin-8 activity.…”
Section: New Endoscopic Techniques 1 Chromoendoscopy and Magnifying mentioning
confidence: 88%
“…Nishio et al [16] reported that magnifying-colonoscopy (MCS) grade was associated with the degree of histological inflammation and mucosal IL-8 activity in quiescent patients with ulcerative colitis, and might predict the probability of subsequent disease relapse in patients with ulcerative colitis in remission. Magnifying colonoscopy was performed in 113 patients in remission, and the relationship between pit patterns, IL-8 activity, and histological disease activity was evaluated.…”
Section: Magnifying Chromoscopic Findings and Prediction Of Relapsementioning
confidence: 99%
“…Although MCS grade positively correlated with histological grade and mucosal IL-8 activity, these latter parameters were less accurate predictors of relapse. One reason may be that they are assessed in biopsy specimens derived from a specific and limited area of colorectal mucosa, whereas magnifying colonoscopy allows the observation of a more extended and representative area, and accordingly greater accuracy by MCS grading [16] . These findings demonstrate the usefulness of MCS in the evaluation of disease activity and in predicting relapse in patients with ulcerative colitis.…”
Section: Magnifying Chromoscopic Findings and Prediction Of Relapsementioning
confidence: 99%
See 1 more Smart Citation